New Polymer Composite Materials III : Selected, peer-reviewed full text papers from the XVII International Scientific and Practical Conference "New Polymer Composite Materials" (NPCM 2021) : selected, peer-reviewed papers from the XVII International Scientific and Practical Conference "New Polymer Composite Materials" (NPCM 2021), July 5-10, 2021, Nalchik, Russian Federation - International Scientific and Practical Conference "New Polymer Composite Materials" (17th : 2021 : Nal'chik, Russia), organiser; Khashirova, Svetlana, editor 642204; Zhansitov, Azamat, editor 642205; Vindizheva, Amina, editor 642206 (Baech, Switzerland : Scientific.Net : Trans Tech Publications Ltd)
This issue of the journal presents materials of the XVII International Scientific and Practical Conference "New Polymer Composite Materials" (NPCM 2021), which was held 5-10 July 2021 in the Kh.M. Berbekov Kabardino-Balkarian State University, Russian Federation. The content of the reports presented reflects the results of research in the field of polymer synthesis and the development of new polymer composite materials, as well as the application aspects arising from them.